Membangun Kerja Sama pada Sistem Jaringan Perpustakaan Umum - Ryzky Amalia Lubis; Vivi Mauliza; Tamara Nur Hasana; Thoyyib Baihaqy; Yusniah Yusniah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Libraries that provide information. Libraries must be able to provide information for users. Libraries must be able to improve collections and services to be able to meet the needs of very diverse users. To increase a very diverse collection, collaboration within the library is needed. Collaboration is carried out in order to improve library collections and services. Because not every library has a complete collection, collaboration between libraries is needed. Collaboration between libraries is an absolute requirement to fulfill library cooperation. By cooperating, it lightens the work in the library and finishes faster. With advances in technology and all-digital, the needs of users are also increasingly sophisticated, such as electronic books, and can borrow online, it doesn't take much time and saves money because you don't have to come to the library. If there is no cooperation between libraries then the library cannot develop and will just go away, both in terms of collections and services in the library there is no improvement. In this journal, it is also explained how the forms of cooperation in library collaboration are inventory, exchange cooperation, working cooperation, facility provision cooperation, cooperation among librarians. In collaboration, there must also be benefits and improvements both in terms of collection and also services from what develops to progress, and in society. With the existence of a cooperative network, it can also meet the needs of various users. Libraries can also continue and increasingly trend. With the continuing development of the needs of various users, the library also requires several librarians to carry out work in the large number of libraries. In research on building cooperation in public library network systems, researchers use descriptive research methods through journals and books which aim to find out an overview of the benefits of building cooperation in public library network systems. Keywords: network system, public library